2019
DOI: 10.1371/journal.pone.0220956
|View full text |Cite|
|
Sign up to set email alerts
|

Multidisciplinary strategies to treat severe hypoglycemia in hospitalized patients with diabetes mellitus reduce inpatient mortality rate: Experience from an academic community hospital

Abstract: Objective Severe hypoglycemia (blood glucose < 50 mg/dl) in hospitalized patients with diabetes mellitus is associated with poor outcomes such as increased mortality and readmission rates. We study the effects of system based interventions in managing severe hypoglycemia and its impact on outcomes. Research design and methods We performed retrospective review of pre- and post- intervention study to quantify severe hypoglycemia in patients admitted in the general interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…We cannot prove causality for these associations, and it may be that hypoglycemia itself is a clinical sign of worsening or severe illness. However, one recent study found that reducing the frequency of inpatient hypoglycemia concomitantly reduced inpatient and 30-day mortality rates ( 53 ). Further trials are needed to determine if direct reduction of ICU hypoglycemia improves clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot prove causality for these associations, and it may be that hypoglycemia itself is a clinical sign of worsening or severe illness. However, one recent study found that reducing the frequency of inpatient hypoglycemia concomitantly reduced inpatient and 30-day mortality rates ( 53 ). Further trials are needed to determine if direct reduction of ICU hypoglycemia improves clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…7 On the other hand, inpatient hypoglycaemia continues to be an important issue associated with poor outcomes. 8 A limited number of studies have investigated the use of glucose-lowering agents other than insulin, such as glucagon-like peptide (GLP-1) receptor agonists, for acute illness, perioperative and critical care areas. 9 In this context, little is known about the efficacy and safety profiles of SGLT2i in hospitalized patients.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 99%
“…18 Standardized reporting, order sets, and hypoglycemia protocols are highly effective to reduce inpatient hypoglycemia. 18,22,23 The widespread use of electronic medical records (EMR), continuous subcutaneous insulin infusion (CSII) pumps, and continuous glucose monitoring (CGM) technology has led to renewed efforts to prevent hypoglycemia by developing automated tools, predictive scores, and remote surveillance. Eight strategies are reviewed below.…”
Section: Prevention Of Hypoglycemiamentioning
confidence: 99%